Distal tibial nonunion using a contralateral anterior L-shaped locking compression plate through a posterior-lateral approach: A retrospective case series. Issue 6 (June 2017) - Lin, Chuanlu; Lin, Lixiang; Vinesh, Lutchooman; Shao, Xiwen; Lu, Xiaolang; Hong, Jianjun
Abstract: Background: Distal tibial nonunion is usually due to severe open distal tibial fractures with high energy injury. The best surgical treatment is not well established because of the poor soft tissue condition. We retrospectively analyzed a series of patients with distal tibial nonunion after severe open distal tibial fractures; our purpose was to introduce a treatment using a contralateral anterior L-shaped locking compression plate through a posterior-lateral approach with Iliac crest bone graft and evaluate the outcomes of patients. Methods: All patients with distal tibial nonunion who received a contralateral anterior L-shaped locking compression plate fixation through the posterior-lateral approach with Iliac crest bone graft by a single surgeon from 2014 to 2016 were reviewed. 9 patients met the criteria. Five of nine patients had varus deformities (range, 9–40°) and 4 patients had valgus deformities (range, 5–30°). Postoperative radiographs, Postoperative complications, limb alignment and limb functional outcome information of AOFAS ankle-hindfoot score were recorded. Results: All patients were followed up for at least 8 months (range, 8–16 months). Union was achieved in all patients after the index surgery without postoperative wound complications while one patient came up with checkrein deformity. Average time to radiographic union was 16 weeks (range, 12–24 weeks). All patients had correction to neutral alignment in both coronal and sagittal planes. The average AOFAS ankle-hindfoot score was 90 (range, 77–100) at the last follow-up of patients. Conclusions: Using a contralateral anterior L-shaped locking compression plate fixation through a posterior-lateral approach with Iliac crest bone graft to reconstruct the distal tibial nonunion is a safe and reliable method that can successfully treat patients with poor soft tissue condition of anterior portion of leg because of its adequate exposure, both tibia and fibula rigid fixation and plenty of bone graft. We believe the application of this method resulting in a high union and low complication rate.